1990
DOI: 10.2337/diab.39.9.1040
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Blood-Brain Barrier Glucose Transporter in Experimental Diabetes

Abstract: Previous studies showing downregulation of blood-brain barrier (BBB) glucose-transporter activity in vivo in experimental diabetes have recently been questioned. Therefore, our investigations examined both the BBB glucose-transporter activity in experimental diabetes in vivo, with the use of the in situ internal carotid artery perfusion technique, and the microvessel glucose-transporter concentration, with quantitative Western immunoblots. These studies show that BBB glucose-transporter activity in vivo is dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(42 citation statements)
references
References 31 publications
0
40
0
2
Order By: Relevance
“…Existing evidence indicates a decreased GLUT-1 activity and glucose clearance in chronic hyperglycemia, with a parallel decrease in expression of GLUT-1 at BBB [46], as confirmed by subsequent studies [47,48]. On the other hand, chronic hypoglycemia increased BBB glucose transport resulting from a concomitant increase in GLUT-1 transcription and expression on lumenal side of brain capillaries [49].…”
Section: Discussionmentioning
confidence: 66%
“…Existing evidence indicates a decreased GLUT-1 activity and glucose clearance in chronic hyperglycemia, with a parallel decrease in expression of GLUT-1 at BBB [46], as confirmed by subsequent studies [47,48]. On the other hand, chronic hypoglycemia increased BBB glucose transport resulting from a concomitant increase in GLUT-1 transcription and expression on lumenal side of brain capillaries [49].…”
Section: Discussionmentioning
confidence: 66%
“…The first report showing a decrease in blood-brain glucose transfer in rats with chronic hyperglycemia was published in 1981 using an intravenous bolus infusion method [103]. Later, findings of this study were subsequently confirmed by several investigators using different experimental approaches [97,104–106]. Differences in the techniques utilized and inherent problems in calculating glucose transfer rates using these techniques were detailed in peer review by Pelligrino et al .…”
Section: Diabetes: Glucose Metabolism and Glucose Transporters In mentioning
confidence: 70%
“…This suggests that the biological answer to chronic excess of glucose in the systemic circulation should be down regulation of its transporters. In this line, many experimental studies report a down-regulation of BBB glucose transporters in hyperglycemic animals [63,78,79], indicating the measures taken by brain from preventing excessive glucose intake. However, this is not a universal scientific consensus since other studies (in both animals and humans) did not reveal significant changes in the BBB glucose transporters expression in DM [41,80-83].…”
Section: Effect Of Hyperglycemia On Bbb Glucose Transport In Dmmentioning
confidence: 99%